Could histoplasma capsulatum be related to healthcare-associated infections? - Carreto-Binaghi, Laura Elena; Damasceno, Lisandra Serra; Pitangui, Nayla de Souza [UNESP]; Fusco-Almeida, Ana Marisa [UNESP]; Mendes-Giannini, Maria José Soares [UNESP]; Zancope-Oliveira, Rosely Maria; Taylor, Maria Lucia (Hindawi Publishing Corporation, 2015)
Healthcare-associated infections (HAI) are described in diverse settings. The main etiologic agents of HAI are bacteria (85%) and fungi (13%). Some factors increase the risk for HAI, particularly the use of medical devices; patients with severe cuts, wounds, and burns; stays in the intensive care unit, surgery, and hospital reconstruction works. Several fungal HAI are caused by Candida spp., usually from an endogenous source; however, cross-transmission via the hands of healthcare workers or contaminated devices can occur. Although other medically important fungi, such as Blastomyces dermatitidis, Paracoccidioides brasiliensis, and Histoplasma capsulatum, have never been considered nosocomial pathogens, there are some factors that point out the pros and cons for this possibility. Among these fungi, H. capsulatum infection has been linked to different medical devices and surgery implants. The filamentous form of H. capsulatum may be present in hospital settings, as this fungus adapts to different types of climates and has great dispersion ability. Although conventional pathogen identification techniques have never identified H. capsulatum in the hospital environment, molecular biology procedures could be useful in this setting. More research on H. capsulatum as a HAI etiologic agent is needed, since it causes a severe and often fatal disease in immunocompromised patients.